Multilevel green space ecological network collaborative optimization from the perspective of scale effect - Zhou, Yuan; Yao, Jing; Li, Pengyao; Li, Bei; Luo, Yushu; Ning, Shunbin (Ecological indicators, 2024)
[Display omitted] •Proposed a multiscale hierarchical ecological network framework based on scale effect.•Optimal granularity threshold specified by landscape pattern index fitting function.•Integrated circuit theory and hydrological model for multiscale ecological networks.•Adopted scale nesting and hierarchical transmission to construct multiscale networks.•Proposed a multiscale green space ecological security pattern for restoration. With rapid urbanization, the conflicts between economic development and environmental protection have become increasingly complex and exhibit multiscale characteristics. Constructing a green space ecological network (EN) is an effective approach to alleviate urban ecological issues and maintain regional ecological security. However, traditional EN research often focuses on a single scale, neglecting multiscale nesting and collaborative optimization of landscape elements, particularly the importance of spatial granularity. To address this deficiency, this study proposed a multiobjective, multiscale nested green space EN framework for Chengdu, China. Using landscape pattern index fitting functions, morphological spatial pattern analysis, the connectivity index, circuit theory, hydrological analysis model, scale nesting, and hierarchical transmission theories, a multiscale coupled synergistic and hierarchical optimization regional green space ecological security pattern (ESP) was developed. Analysis of the derived results revealed the following. ① With increasing granularity, the landscape pattern indices showed overall increasing, overall decreasing, and overall fluctuating trends. The optimal granularity threshold for large, medium, and small scales was 9, 6, and 3 m, respectively. ② Overall, 92, 66, and 88 ecological sources; 403, 278, and 321 ecological corridors; 72, 77, and 47 pinch points; 96, 94, and 88 barriers; and 182, 120, and 87 ecological nodes were identified in the city, central city, and old city areas, respectively. ③ The ENs demonstrated reasonable hierarchical nesting characteristics, essential for interscale material and energy circulation. There were 9 overlapping ecological sources with total area of 18.34 km2 and 47 overlapping corridors with total length of 53.37 km. These overlapping areas were key regions for ensuring stability in the overall regional ESP and continuity in biological processes, and should be given priority protection. In addition, there were also 19 overlapping pinch points, 12 overlapping barriers, and 4 ecological nodes that accounted for 26.39 %, 24.68 %, and 40.43 % of the total pinch points; 12.50 %, 12.77 %, and 13.64 % of the total barriers; and 2.20 %, 3.33 %, and 4.60 % of the total ecological nodes in the city area, central city area, and old city area, respectively. The high overlap of ecological strategic points across scales indicated cross-scale continuity of biological processes. ④ Enhancing the habitat quality of land types such as forest land, green spaces, grassland, and water bodies is crucial for restoration of ecological corridors and strategic points. Constructing a multiscale hierarchical linkage framework and formulating cross-scale pattern optimization and coordination schemes can effectively address ecological issues. The multiscale nested and synergistic green space ESP, constructed from the “source–corridor–strategic-point–network” framework, enhances the connectivity of regional landscape elements, increases energy flow efficiency, and strengthens spatial stability. The results provide methodological support for strategic policymaking focused on ecological spatial governance of an urban ecological protection at multiple levels.